Uncleanliness at the larger scale: the problems of Global Capitalism - Zamri, Zahid (IIUM Press, 2022)
The issues of uncleanliness have always been seen from the angle of individuals as the subjects that are responsible for the problem. Such clichés have overshadowed the much bigger subject that should be put into question which is the global capitalism. Basically, global capitalism is an advance-universalized capitalist system that supersedes the previous non-transnational capitalist mode of production. Along the process, as the hegemonic global system, it has produced not only commodities but also “common sense” that diverts the responsibility to protect the environment from the capitalists’ shoulders towards the masses - in this case on issues related to uncleanliness in human societies e.g. the devastating accumulation of plastic waste, river and air pollution, oil spills at sea, etc. The article attempts to look at the general common sense held by the public as the means that has been manipulated by the global capitalists within the cultural, political and economic spheres in relation to the problem of uncleanliness of our mother nature. Then it argues for more attention to be given on this issue by intellectuals and activists alike on this issue as well as demanding for their will to change the status-quo. It is also hope that the article will disillusion the general public that we have been merely focusing on the symptomatic problems and not the main systemic factor that contributes to such problems. Thus it calls for change in our problem-solving approach when dealing with such issues.